Biophysical and Functional Characterization of Rhesus Macaque IgG Subclasses - Boesch, Austin W.; Osei-Owusu, Nana Yaw; Crowley, Andrew R.; Chu, Thach H.; Chan, Ying N.; Weiner, Joshua A.; Bharadwaj, Pranay; Hards, Rufus; Adamo, Mark E.; Gerber, Scott A.; Cocklin, Sarah L.; Schmitz, Joern E.; et al. (Frontiers in Immunology, 2016)
Antibodies raised in Indian rhesus macaques (Macaca mulatta, MM) in many preclinical vaccine studies are often evaluated in vitro for titer, antigen-recognition breadth, neutralization potency, and/or effector function, and in vivo for potential associations with protection. However, despite reliance on this key animal model in translation of promising candidate vaccines for evaluation in first in man studies, little is known about the properties of MM IgG subclasses and how they may compare to human IgG subclasses. Here we evaluate the binding of MM IgG1, IgG2, IgG3, and IgG4 to human FcγR and their ability to elicit the effector functions of human FcγR-bearing cells, and unlike in humans, find a notable absence of subclasses with dramatically silent Fc regions. Biophysical, in vitro, and in vivo characterization revealed MM IgG1 exhibited the greatest effector function activity followed by IgG2 and then IgG3/4. These findings in rhesus are in contrast with the canonical understanding that IgG1 and IgG3 dominate effector function in humans, indicating that subclass-switching profiles observed in rhesus studies may not strictly recapitulate those observed in human vaccine studies.